Inhibition of the Hedgehog pathway in lung cancer. (July 2019) - Dimou, A.; Bamias, A.; Gogas, H.; Syrigos, K.
Highlights: GLI transcription factors are frequently expressed in various lung cancer types. Both canonical Hedgehog signaling and other pathways activate GLI in lung cancer. Activation of the Hedgehog pathway often occurs upon development of resistance. Clinical trials of Smoothened inhibitors in Small-Cell Lung Cancer were negative. Further research is required with new agents in molecularly defined subgroups. Abstract: Inhibitors of the hedgehog pathway are effective in patients with basal cell carcinoma and a subgroup of patients with medulloblastoma with active hedgehog signaling. Despite preclinical work suggesting otherwise, clinical trials in solid tumors of epithelial origin have not shown added benefit with these drugs. Here, we review the preclinical and clinical data of hedgehog pathway inhibition in the most common histologic types of lung cancer. We focus on highlighting areas of uncertainty, where further research might define a niche for hedgehog pathway inhibition in patients with lung cancer.